Subjek Religius dalam Algoritma Masyarakat Digital - Takbir, Muhammad; Mirandy, Iin Safira (PAPPASANG, 2025)
Digital technological development has had a significant impact on various aspects of life, including in the realm of spirituality and religious experience. Algorithms, as the core of modern digital systems, now play a central role in shaping the way individuals access, understand, and express spiritual values. More than just technical devices, algorithms function as cultural mechanisms that actively construct and represent religious subjects according to platform logic and market interests. This article aims to analyze how religious subjects are constructed and determined by algorithmic logic using philosophy of existentialism as approach. The focus of the discussion includes the crisis of authenticity, the commodification of religiosity, and the emergence of the possibility of ethical resistance to algorithmic determination. In this context, digital space often traps spirituality in a shallow and easily consumed format, obscuring the depth of authentic religious meaning. However, this study also reveals that there is still potential for religious subjects to reclaim the space of reflection and spiritual meaning through conscious and ethical actions. Thus, digital space can be read not only as a field of technological domination, but also as an arena for contestation of meaning and spiritual liberation that allows for a more authentic religious subjectivity Perkembangan teknologi digital telah membawa dampak signifikan terhadap berbagai aspek kehidupan, termasuk dalam ranah spiritualitas dan pengalaman religius. Algoritma, sebagai inti dari sistem digital modern, kini memainkan peran sentral dalam membentuk cara individu mengakses, memahami, dan mengekspresikan nilai-nilai spiritual. Lebih dari sekadar perangkat teknis, algoritma berfungsi sebagai mekanisme kultural yang secara aktif mengonstruksi dan merepresentasikan subjek religius sesuai dengan logika platform dan kepentingan pasar. Artikel ini bertujuan untuk menganalisis bagaimana subjek religius dikonstruksi dan ditentukan oleh logika algoritmis dengan menggunakan pendekatan filsafat eksistensialisme. Fokus pembahasan mencakup krisis otentisitas, komodifikasi religiusitas, serta kemungkinan lahirnya resistensi etis terhadap determinasi algoritmik. Dalam konteks ini, ruang digital kerap menjebak spiritualitas dalam format yang dangkal dan mudah dikonsumsi, mengaburkan kedalaman makna religius yang autentik. Namun demikian, kajian ini juga mengungkap bahwa masih terdapat potensi bagi subjek religius untuk merebut kembali ruang refleksi dan pemaknaan spiritual melalui tindakan sadar dan etis. Dengan demikian, ruang digital dapat dibaca tidak hanya sebagai medan dominasi teknologi, tetapi juga sebagai arena kontestasi makna dan pembebasan spiritual yang memungkinkan subjektivitas religius yang lebih otentik.